Starting on unequal footing: an investigation into the effects of home language on academic performance - Leong, Alyssa Mann Yee (Nanyang Technological University, 2023)
Past research suggests language and academic achievement are closely related. Notably, students exposed to the language of instruction at home tend to fare better academically than their peers who do not. Granted, this relationship has been ambiguous and laden with complexities, from students’ socio-economic standing (SES) to parental involvement. While individual correlations have been found between SES and academic performance, and home language and SES in Singapore’s context, the correlation between language and academic performance has yet to be explored. Therefore, the present study endeavoured to uncover this relationship through an online questionnaire with 219 participants, and follow-up interviews with interviewees spanning diverse SES and education backgrounds. Results showed that home language and performance on standardised national examinations are significantly correlated, where those who predominantly speak a non-English language at home tend to perform worse than those whose dominant home language is English. SES, in particular, plays a considerable role in influencing the effects of home language on academic performance. Overall, the results of this study suggest that different home language environments and SES place individuals at varying starting points, and can influence academic performance, in spite of Singapore’s supposed meritocratic system.